Pengaruh Content Marketing dan Influencer Marketing Terhadap Keputusan Pembelian Produk Skintific dengan Content Creation sebagai Variabel Intervening (Studi Kasus pada Pengikut Cut Rizki) - Firdausi, Fitri Fathia (Master of Management Diponegoro University, 2024)
The development of technology has a major influence on the world of marketing. The phenomenon of the ease of using the internet and social media has led to the emergence of an unrealistic paradigm of beauty embedded in Indonesia, where women are required to be physically perfect, caused by society, family, friends, and the media. Instagram and Tiktok influencer Cut Rizki, often provides a voice in breaking down these beauty standards and motivating women to take care of their skin. And provides motivation that taking care of the skin is a form of self-love, not to cover up insecurity. So this study aims to analyze the effect of Content Marketing and Influencer Marketing on Purchasing Decisions for Skinific Products with Content Creation as an Intervening Variable. Conducted to 100 respondents, Cut Rizki's Instagram and Tiktok female followers who used Skintific products at least 2x in the last 6 months. The data analysis method used is SEM SmartPLS 3.0. The results found were: 1) Content Marketing has a positive and significant effect on the Content Creation variable; 2) Influencer Marketing has a positive and significant effect on Content Creation; 3) Content Marketing has no positive and significant effect on Purchasing Decisions; 4) Influencer Marketing has no positive and significant effect on Purchasing Decisions; 5) Content Creation has a positive and significant effect on Purchasing Decisions; 6) Content Marketing has a positive and significant effect on Purchasing Decisions through Content Creation; 7) Influencer Marketing has a positive and significant effect on Purchasing Decisions through Content Creation.